MODEL KEPEMIMPINAN PENDIDIKAN DALAM MENINGKATKAN KINERJA ORGANISASI SEKOLAH: TINJAUAN LITERATUR - Indah Meiliana; Suhernan; Muhamad Taufik; Muhammad Hasan Basari (JIP: Jurnal Ilmu Pendidikan, 2025)
Educational leadership in schools is a very important factor in improving the quality of education. Effective leadership can influence teacher motivation, productivity, and performance, as well as improve student academic achievement. However, many schools still face difficulties in developing effective educational leadership. The purpose of this study is to gain a deeper understanding of educational leadership in schools. This study uses a literature review method in the form of several journals and books on leadership. The results of the study show that educational leadership must be responsive to developments and changes in the world of education. Leaders must be able to integrate technology, face global challenges, and manage policy changes wisely. A leader must also be able to collaborate with teachers, staff, and parents. The implications of this research are to improve the quality of educational leadership in schools, raise public awareness of the importance of educational leadership, and develop teachers' abilities in classroom management and teaching.